STUDI ETNOGRAFI: PRAKTIK BUDAYA PEMBERIAN ASI EKSKLUSIF DENGAN RISIKO KEJADIAN STUNTING PADA MASYARAKAT SUKU MBOJO DI DESA SAMBORI - Fadila Putri, Kiki; Noris, M.; Iksan, Muammar; Hairunnisah, Hairunnisah (Lafadz Jaya Publisher, 2026)
Exclusive breastfeeding practices in indigenous communities are often influenced by cultural values, traditions, and belief systems that may affect the risk of stunting among children. This study aimed to analyze cultural practices related to exclusive breastfeeding and their association with stunting risk among the Mbojo ethnic community in Sambori Village. This study employed a quantitative approach with an analytical survey design. The study population consisted of mothers with children under five years of age in Sambori Village, with 32 respondents selected based on the research criteria. Data were collected using a Likert-scale questionnaire consisting of 13 statements. Data analysis was conducted using SmartPLS, including outer loading, construct reliability and validity, discriminant validity, path coefficient, R-Square, f-Square, and Pearson correlation analyses. The results revealed that Traditional Maternal and Childcare Practices had the strongest positive effect on Stunting Risk (β = 0.909), followed by Culture and Modern Health System (β = 0.742). In contrast, Breastfeeding Practices (β = -0.625) and Maternal Belief Systems (β = -0.405) showed negative effects on Stunting Risk. The R-Square value of 0.582 indicated that the model explained 58.2% of the variance in stunting risk. The study concludes that cultural factors, childcare traditions, and breastfeeding practices play significant roles in shaping stunting risk, highlighting the importance of culturally sensitive nutrition and health interventions.